Primary School Pupils ' Acquisition of Environmental Education in Moshi Rural District in Tanzania - Ndeskoi, Thaudensia Ndeskoi Ndeskoi (Papers in Education and Development, 2022)
The main focus of this study was to assess the acquisition of environmental education among primary school pupils in Moshi Rural district in Tanzania. The study employed a mixed methods research approach with a sample size of randomly selected 235 pupils. Data were collected through questionnaires, focus group discussions, documentary review and nonparticipant observation. Results show that majority of pupils had average knowledge and awareness of environmental issues. Also, environmental education offered in schools was considered important. Various sources of environmental education were used to obtain environmental information among the pupils. Moreover, there was considerable evidence of several environmental accomplishments demonstrated at schools and homes. The study concludes that envionmental education acquired in schools is indispensable for creating environment-related knowledge in life. Keywords: environmental behaviour, environmental knowledge, environmental literacy